2017
DOI: 10.1097/mib.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Maintenance of Clinical, Endoscopic, and Radiographic Response to Ustekinumab in Moderate-to-Severe Crohnʼs Disease

Abstract: Subcutaneous ustekinumab is an effective treatment option for maintaining long-term clinical, endoscopic, and radiographic response in patients with moderate-to-severe CD failing antitumor necrosis factor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 29 publications
6
98
1
3
Order By: Relevance
“…In contrast, patients with an HBI score ≥ 7 at induction were less likely to achieve clinical response, as were patients with stricturing disease . The same group performed a retrospective cohort study of 104 CD patients who responded to ustekinumab induction and continued long‐term maintenance . Colonic and ileocolonic disease were associated with lower risk for loss of response during maintenance therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, patients with an HBI score ≥ 7 at induction were less likely to achieve clinical response, as were patients with stricturing disease . The same group performed a retrospective cohort study of 104 CD patients who responded to ustekinumab induction and continued long‐term maintenance . Colonic and ileocolonic disease were associated with lower risk for loss of response during maintenance therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Concomitant use of immunosuppressant at baseline was a predictive factor of clinical benefit at 3 months . Ma et al found that concurrent immunomodulator was associated with a reduced risk of loss of response during maintenance treatment but not for induction . However, Battat et al showed similar rates of steroid‐free clinical remission, endoscopic response and remission between patients with or without immunomodulator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are a few limitations to consider. First, this study only included follow‐up data up to 14 weeks, which is a shorter follow‐up period than a similar previous study by Ma et al. Also, HBI was used to assess clinical response and remission, whereas the UNITI trial used the Crohn's Disease Activity Index.…”
mentioning
confidence: 97%
“…Currently, the biologics with regulatory approval for the management of CD include TNF antagonists and ustekinumab, a monoclonal antibody blocking the biological activity of IL-12 and IL-23 [18,19] . Bmi1 expression correlated significantly with TNF-α and IL-23 expression, with a linear coefficient of 0.49 and 0.48, respectively in the colonic mucosa of CD patients ( Fig.…”
Section: Association Between Bmi1 and Cytokines In The Colonic Mucosamentioning
confidence: 99%